1984
DOI: 10.1063/1.864893
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlation measurements in a turbulent boundary layer above a rough wall

Abstract: Cross correlation between signals from a wall probe and a hot-wire probe indicates that large structures, inclined to the wall at approximately 20 °, exist in a rough-wall boundary layer as reported earlier by Brown and Thomas and by Head and Bandyopadhyay for a smooth wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…Brown and Thomas (1977) crosscorrelated signals from a wall probe with u signals in a smoothwall boundary layer, finding that the maximum correlation occurred along a line in the xz plane sloping obliquely with the flow at an angle of about 18° to the horizontal. Comparable rough-wall data have been obtained by Bessem and Stevens (1984) and Osaka et al (1984), over "k-type" and "d-type" walls, respectively; in both cases, the locus of maximum u correlation was similar to that found by Brown and Thomas.…”
Section: Organized Motion In Rough-wall Boundary Layerssupporting
confidence: 66%
“…Brown and Thomas (1977) crosscorrelated signals from a wall probe with u signals in a smoothwall boundary layer, finding that the maximum correlation occurred along a line in the xz plane sloping obliquely with the flow at an angle of about 18° to the horizontal. Comparable rough-wall data have been obtained by Bessem and Stevens (1984) and Osaka et al (1984), over "k-type" and "d-type" walls, respectively; in both cases, the locus of maximum u correlation was similar to that found by Brown and Thomas.…”
Section: Organized Motion In Rough-wall Boundary Layerssupporting
confidence: 66%
“…The outer-layer structural consistency between smooth-and rough-wall flow observed by Bessm & Stevens (1984) is in accordance with the many aforementioned studies that support the proposition of outer-layer similarity in the turbulence statistics for rough-wall turbulence. In support of this similarity, many other studies have observed little difference in the spatial velocity correlations of smooth-and rough-wall flow outside the roughness sublayer.…”
Section: Roughness Effects In the Outer Layersupporting
confidence: 76%
“…Bessm & Stevens (1984) studied the inclination angle of large-scale structures in a turbulent boundary layer over a k-type grooved surface via measurements of the cross-correlation between the wall shear stress and streamwise velocity for 0.05 < y/J < 0.75. An inclination angle of approximately 20' was observed which is consistent with the results of Brown & Thomas (1977) and Head & Bandyopadhyay (1981) for smooth-wall turbulence.…”
Section: Roughness Effects In the Outer Layermentioning
confidence: 99%
“… Gurnett et al [1983] cite laboratory experiments in developing methods of recognizing the presence of dust grains near Saturn [ Adams and Smith , 1971; Friichtenicht , 1964; Grün , 1981]. LaBelle and Kintner [1989], in discussing the measurement of wavelength in space plasmas, point to the routine use of cross‐correlation analysis in laboratory experiments [ Gresillon and Doveil , 1975; Gresillon et al , 1975; Bessem and Stevens , 1984].…”
Section: Laboratory Results Cited By Space Researchersmentioning
confidence: 99%
“…Langmuir probes [ Mott‐Smith and Langmuir , 1926] have evolved into floating‐bias probes for measuring DC [ Smith et al , 1979] and AC [ Sprott , 1966] values of electrostatic (“space”) potential, swept‐bias probes for determining electron temperature from the functional form of collected current versus bias, fixed‐bias probes for inferring plasma density and its fluctuations from the DC and AC values of collected current, and single‐sided probes for directional analysis of velocity distribution functions. Cross‐correlation analysis for coordinate space was developed by Gresillon and Doveil [1975], Gresillon et al [1975], and Bessem and Stevens [1984]. Cross‐spectral analysis for the frequency domain was developed by Harker and Ilić [1974] and Ilić [1975].…”
Section: Benefits Of Laboratory Experiments To the Understanding Of Smentioning
confidence: 99%